Corumination, diet culture, intuitive eating, and body dissatisfaction among young adult women. Issue 2 (21st December 2020) - Faw, Meara H.; Davidson, Kenzie; Hogan, Laura; Thomas, Kayla
Abstract: Body dissatisfaction is pervasive among women in the United States. As a result, women feel pressured to participate in body‐related corumination. In response to evidence suggesting that diet culture and body‐related corumination can produce significant harm, scholars have increasingly proposed intuitive eating as a body‐positive alternative. This study explores the relationships between body‐specific corumination, body dissatisfaction, friendship quality, and intuitive eating. Results from this study's mixed‐methods investigation suggest that increase body‐related corumination is associated with increased body dissatisfaction and decreased intuitive eating. Relationship quality is associated with intuitive eating, and intuitive eating is negatively associated with body dissatisfaction. Results from this study's qualitative data indicate that women experience body‐related conversations in specific ways that can enforce unhealthy patterns of behavior and conversation.